PERANCANGAN SISTEM INFORMASI KASIR BERBASIS WEB (Studi Kasus : Toko Sari) - Rian Rifai; Fajar Agung Nugroho (CV. Multi Kreasi Media, 2024)
In the era of technological development, Toko Sari still uses books to carry out its business activities, so that in calculations, checking inventory, inputting goods and all data processing processes become less effective, thus making the process take a lot of time. Based on the problems above, it is necessary to create a web-based application that can help sales at Toko Sari. What is done in this system displays sales, purchases, item data and reports according to needs. In making this system using the waterfall method. The purpose of making this cashier operating system is to make it easier for shop owners to make transactions, check stock data of goods and provide information on sales reports and purchase reports at the store.